Does Carbon Performance and Green Investment Affect Carbon Emissions Disclosure? - Manurung, Daniel T H; Hidayah, Nurul; Setiany, Erna; Saputra, Komang Adi Kurniawan; Hapsari, \\ Dini Wahjoe (Journal of Environmental Accounting and Management, 2026)
The importance of corporate governance is to direct the company's management professionally and responsibly, including the issue of carbon emissions. This study was conducted to achieve objectives related to the effects of Corporate Governance on the company's carbon emission disclosures. The research was conducted on 40 non-financial companies in 2015-2019. Company data is obtained from the Indonesia Stock Exchange. The study used purposive sampling, an analytical tool that used multiple linear regression. The study results show that companies that have information about, Corporate Governance: Board Independence and Board Committee will be able to disclose carbon emissions. This research implies that the company tends to disclose carbon emissions produced by the company so that government policy that lasts at the same time is needed to improve disclosure compliance.